2016
DOI: 10.1093/ageing/afv200
|View full text |Cite
|
Sign up to set email alerts
|

VALFORTA: a randomised trial to validate the FORTA (Fit fOR The Aged) classification

Abstract: DFG-German Research Foundation (WE 1184/15-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 22 publications
4
101
0
23
Order By: Relevance
“…In a randomized, controlled trial (VALFORTA) FORTA significantly improved medication quality as measured by the FORTA-score that adds over-and undertreatment errors. FORTA also reduced adverse drug effects at a number needed to treat of only 5 [11].…”
mentioning
confidence: 99%
“…In a randomized, controlled trial (VALFORTA) FORTA significantly improved medication quality as measured by the FORTA-score that adds over-and undertreatment errors. FORTA also reduced adverse drug effects at a number needed to treat of only 5 [11].…”
mentioning
confidence: 99%
“…The updates of already existing lists and new lists of PIM are creating a need for constant updates of the content of this repository. For example, between the creation of the repository and the publication of this paper, an update of the FORTA list was published along with a number of validation studies . Although the author of the list describes the FORTA list as an implicit tool, we consider that this list contains valuable information and it needs to be considered for inclusion in the next updated more searchable version of this repository.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that listing approaches such as START/STOPP or FORTA include aspects of fall risk reduction, as FRIDs are mostly highlighted as causative factors. Interventional trials have shown that these systematic drug-optimization strategies can reduce drug side effects [31, 32], including falls [20]. However, no single ideal tool exists currently, and the choice of tool may rely on the purpose of use and availability of data [30, 33].…”
Section: How To Reduce the Use Of Fall-risk-increasing Drugs (Frids)?mentioning
confidence: 99%